The Effect of Working Capital Management on Profitability in Manufacturing Companies Listed on the Indonesia Stock Exchange - Kristiana, Dina; Karnasi, Reniati (PT. EQUATOR SINAR AKADEMIA, 2024)
The purpose of this study was to determine the effect of working capital on Return on Asset and Return on Equity in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Working capital is measured by accounts receivable, inventory, accounts payable, and the cash conversion cycle, while profitability is measured by return on assets and return on equity. This research is a quantitative research with a research design in the form of hypothesis testing. The analytical method in this study uses multiple regression analysis using E-views 10.0 software. The data is obtained from the financial reports of manufacturing companies that have been published and listed on the Indonesia Stock Exchange (IDX) for 2018-2022. The sample in this study was taken using a purposive sampling technique, namely 127 manufacturing companies that have been published and listed on the Indonesian Stock Exchange (IDX). The results of the study show that the variables accounts receivable and inventory have a significant negative effect on return on assets, while the account payable and cash conversion cycle variables have no effect on return on assets and return on equity.